Синтез структури пристрою керування тяговим електроприводом рухомого складу міського електротранспорту з врахуванням зміни умов зчеплення - Грабко, В. В.; Проценко, Дмитро Петрович (НТУ "ХПІ", 2010)
In work, using a mathematical apparatus of sequences, the structure of the device for management of the traction electric drive of a rolling stock of city electric transport is synthesized taking into account change of conditions of coupling which allows to warn development of slipping and to raise hauling-coupling properties.
Synthesis of structure of the control mean by the traction electric drive of the rolling stock of city electric transport taking into account change of conditions of coupling
Keywords: коефіцієнта зчеплення; буксування; модель математична; реле обмежувальне